Are we under-diagnosing Hepatitis C in children in Scotland?. (24th May 2012) - Pollock, L; McLeod, A; Doherty, C; Hague, R
Abstract : Aim: Hepatitis C virus (HCV) is a major public health problem in Scotland. Under-diagnosis in adults is well recognised, with almost 60% of HCV-infected persons unaware of their status. The epidemiology of HCV in children in Scotland is not well studied. This study aims to compare predicted prevalence of vertically transmitted HCV to actual number of diagnosed cases in children born in Scotland between January 1991 and December 2008. Methods: A crude model was used to estimate the prevalence of vertically transmitted HCV infection in children born in Scotland 1991-2008: a. Estimated prevalence of maternal HCV infection 0.29% (95% CI 0.23-0.36%) x number of registered births (Jan 1991- Dec 2008) = Number of infants potentially exposed to HCV b. No of infants potentially exposed to HCV x vertical transmission rate (5%) = Total expected number of vertically transmitted HCV-infected infants in Scotland (1991-2008) Estimated maternal seroprevalence was based on published national Scottish neonatal HCV seroprevalence data from 2000. Vertical transmission rate was based on the European Paediatric HCV Network 'best estimate' from large European transmission studies. The Health Protection Scotland (HPS) Blood Borne Virus database was used to identify all cases of HCV in children under 16 years diagnosed between January 1991 and December 2010. Results: Of 1, 040, 219 live births in Scotland from Jan 1991- December 2008 an estimated 3017 (range based on 95% CI 2393-3745) were to HCV infected mothers. 151 (120-187) infants were predicted to be infected with HCV. The predicted prevalence rate of vertically transmitted HCV in Scotland was 1.4/10000 (1.1-1.8/10000) live births. The actual number of diagnosed cases in Scottish children born 1991-2008 identified from the HPS database was 57, an observed HCV prevalence rate of 0.5/10000 live births. There was a 62% (52-70%) deficit between predicted and diagnosed cases. Conclusions: There is a significant deficit between predicted and diagnosed cases of HCV in children in Scotland. This could indicate under-diagnosis. Targeted antenatal screening could potentially identify undiagnosed women and infants at risk of HCV. Large population based paediatric seroprevalence studies are required to establish the true prevalence of HCV in Scotland.